1.3k views
9 votes
Step 1: 12x – 15 – 12x = 7x + 20

Step 2: 12x – 12x – 15 = 7x + 20
Step 3: -15 = 7x + 20
Step 4: -35 = 7x
Step 5: -5 = 3
Drag and drop the correct justification for each step.

User Laycat
by
5.4k points

1 Answer

3 votes

Explanation:

step 1. 12x - 15 - 12x = 7x + 20

step 2. 12x - 12x - 15 = 7x + 20 (grouping of terms)

step 3. -15 = 7x + 20 (adding like terms)

step 4. -35 = 7x (subtract 20 from both sides)

step 5. this step is incorrect.

step 6. -5 = x ( divide both sides by 7)

step 7. x = -5 (put the variable first).

User Jane S
by
5.9k points